EXTRA FLEXIBLE TACTICAL CABLE. - Rigling, Walter S. (1966)
This document is the ninth quarterly progress report of a program to develop a family of lightweight, small diameter, highly flexible, multiconductor cables to meet current and anticipated operational requirements of Army Equipment in Arctic and tropical environments. The cables shall be air transportable and suitable for use with widely dispersed and highly mobile tactical equipments. New Class H cable designs with a unidirectional lay and polyester tape insulation were fabricated. Test results for the new designs show considerable improvement in mechanical strength over the original designs which were fabricated with a reverse lay. Initial test results on the Class F cable (26 pair) tend to indicate also, the superiority of unidirectional lay construction over reverse lay for both bend and twist tests. (Author)